Thermal behaviour of some polymethacrylates with a 1,3-dioxolane ring - Ilter, Z; Çoskun, M; Erol, I; Ünal, A; Ahmedzade, M (Elsevier Sci Ltd, 2002)
(2-Cyclohexylidene-1,3-dioxolane-4-yl)methyl methacrylate and (2-cyclopentylidene-1,3-dioxolane-4-yl)methyI methacrylate prepared from the reaction of glycidyl methacrylate with cyclohexanone and cyclopentanone, have been polymerised by benzoyl peroxide. Spectroscopic characterization of the monomers and their homopolymers have been done by Fourier transform infrared (FT-IR) and H-1 and C-13 nuclear magnetic resonance (NMR) spectroscopies. Thermal degradation of the polymers has been studied by thermogravimetric analysis and FT-IR. Volatile products of the degradation have been investigated by FT-IR, H-1 and C-13 NMR and gas chromatography-mass spectrometry techniques. Total degradation of the polymers to 450 degreesC produces extensively the monomers, especially degradation of poly[(2-cyclohexylidene-1,3-dioxolane-4-yl)methyl methacrylate]. The degradation products and the mechanism are discussed. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Degradation; Methacrylate>